The role of DNA methylation on transcription factor occupancy and transcriptional activity - Cusack, M (2017)
DNA methylation is an epigenetic mark that is deposited throughout the genome of mammals and plays an important role in the maintenance of transcriptionally repressive states across cell divisions. There are two major mechanisms by which DNA methylation has been proposed to act: one involves the recognition of the mark by protein complexes containing histone deacetylases (HDACs) that can remodel the local chromatin. Alternatively, methylation has been suggested to directly affect the interaction between transcription factors and their cognate binding sequence. The aim of this research was to determine the contributions of these two mechanisms in cells. The importance of HDAC activity in mediating DNA methylation-dependent transcriptional repression was assessed by comparing the genes and retrotransposons that are upregulated in response to DNA methylation loss or the disruption of HDAC activity. To this purpose, we performed whole-genome transcriptional analysis in wild type and DNA methylation-deficient mouse embryonic stem cells (DNMT.TKO mESCs) in the presence and absence of the HDAC inhibitor trichostatin A. Our data suggests that there are few genes whose repression is solely dependent on the recruitment of HDACs by DNA methylation in mESCs. Rather it appears that DNA methylation and HDAC-mediated silencing represent two independent layers of repression that converge at certain transcriptional elements. To investigate the contribution of DNA methylation on the genome-wide occupancy of transcription factors, we compared the global chromatin accessibility landscape and the binding profile of candidate transcription factors in the absence or presence of DNA methylation. We found that loss of DNA methylation associates with localised gains in accessibility, some of which can be linked to the novel binding of transcription factors such as GABPA, MAX, NRF1 and YY1. Altogether, our results present new insights into the interplay between DNA methylation and histone deacetylation and their impact on the localisation of transcription factors from different families.